Amour fou [videorecording] - Hausner, Jessica; Schnöink, Birte, 1984-; Friedel, Christian, 1979-; Grossmann, Stephan, 1971- (Film Movement series, 2015)
Forever under-appreciated and melancholy, Heinrich is a young poet in Romantic Era Berlin who determines his best way out of despair is to end it all, and he sets about finding a woman to join him in his predetermined departure. Recently diagnosed with a terminal illness, the well-off but unremarkable Henrietta, fascinated by Heinrich's controversial "The Marquise of O," finds his offer intriguing, if a bit strange.